2014
DOI: 10.5173/ceju.2014.04.art19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about human papillomavirus and the human papillomavirus vaccine in Belgian students

Abstract: IntroductionThe aim of this study was to examine the knowledge of Belgian university students about the human papillomavirus (HPV) and HPV–vaccination.Material and methodsDuring a period of two months we administered an online questionnaire, which contained 29 questions, to 3332 students of the Free University of Brussels. Of the 433 completed questionnaires, 346 were included by age (18–30 years) and completeness of responded questionnaires. These formed the study group.ResultsOf the 346 included questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…About 80% of women who are sexually active are at risk of developing and HPV infection and the peak of incidence of this disease is among young women [3,4]. Some authors have evaluated socio-economic differences and their impact on incidence of oral and oropharyngeal squamossal cell carcinoma and demonstrated that oropharyngeal carcinoma had a strong correlation with HPV [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 80% of women who are sexually active are at risk of developing and HPV infection and the peak of incidence of this disease is among young women [3,4]. Some authors have evaluated socio-economic differences and their impact on incidence of oral and oropharyngeal squamossal cell carcinoma and demonstrated that oropharyngeal carcinoma had a strong correlation with HPV [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…were aware of vaccinations and immunity against this virus, while only 46% knew that HPV could cause anogenital cancer [6]. Chinese researchers assessing student's awareness and acceptance to receive HPV vaccine, showed that 70.8% of students were accepting vaccination, 14.3% of the people had heard about HPV and the most important source of information was public speeches.…”
Section: Introductionmentioning
confidence: 99%
“…Although 44.6% knew that the vaccine also protects against genital warts and it was higher compared to study done among Belgian students (19.4%) [21] and Sadry research group [22], the percentage was expected to be higher since most of the respondents (92%) were from health-care-related courses. HPV vaccination is well known for protection against cervical cancer compared to genital warts and genital herpes though both are caused by certain strains of HPV [22].…”
Section: Discussionmentioning
confidence: 72%
“…Since HPV infection is transmitted directly, the onset of infection may start immediately after sexual intercourse [5]. However, a positive result was shown in studies conducted among college students in Lebanon and Belgium with higher percentages of 66% and 83%, respectively [17,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation